The Six‐item Clock‐Drawing Scoring System: a rapid screening for cognitive impairment in Parkinson's disease. Issue 1 (1st September 2020) - Lolekha, Praween; Tangkanakul, Chanya; Saengchatri, Thanida; Kulkeartprasert, Pornlapat
Abstract : Background: Cognitive impairment, characterised by predominant executive dysfunction and visuospatial deficit, is frequently observed in Parkinson's disease (PD) and may lead to mild cognitive impairment (PD‐MCI) and dementia (PD‐D). The clock‐drawing test (CDT) is a rapid cognitive evaluation that is appropriate for screening frontoparietal lobe dysfunction. This study aimed to evaluate the screening performance of the Six‐item Clock‐Drawing Scoring System (6‐CDSS) in detecting cognitive impairment in PD patients. Methods: A retrospective analysis of free‐drawn clocks from 136 PD patients was performed. The presence of cognitive impairment and dementia was documented by neurologists according to the standard diagnostic criteria. Diagnostic performance and the optimal screening cut‐off scores for cognitive impairment and dementia using the 6‐CDSS were determined. Results: One hundred and thirteen patients were documented as having PD with cognitive impairment (PD‐CI). Of those, 39 were diagnosed as probable PD‐D and 74 with PD‐MCI. The optimal screening cut‐off scores for PD‐CI were 4/5 and 1/2 for probable PD‐D. The area under the receiver operating characteristic curve was 0.88 and 0.91, respectively. Multiple regression analysis revealed that low education levels, poor activity of daily living, and older age were associated with low 6‐CDSS scores. Conclusions: CDT scoring using the 6‐CDSS is a reliable system to screen cognitive impairment in PD and may serve as a simple screening tool for PD‐D in clinical practice.